COMBINED EFFECTS OF WATER DEPTH, ELECTRODE SPACING, AND ADDITIONAL SUBSTRATE IN A SOIL MICROBIAL FUEL CELL FOR SUSTAINABLE BIOELECTRIC (Journal of Energy and Safety Technology (JEST), 2025)
The Soil Microbial Fuel Cell (SMFC) is a technology that utilizes the metabolic activity of soil microorganisms to produce bioelectricity. SMFC provides a sustainable and environmentally friendly energy solution that has the capacity to alleviate the negative consequences of fossil fuel consumption. Unfortunately, there are many factors such as water depth, electrode spacing and types of additional substrate used will affect the performance of a soil microbial fuel cell (SMFC). Therefore, in order to improve and enhance the efficiency of SMFC, factors that contribute to low bioelectricity production need to be studied. In this study, there were 3 different parameters that were investigated for their effect towards the performance of soil microbial fuel cell (SMFC), which were the water depth, electrode spacing and extra substrate types added. SMFC’s configuration in this study was built in a 10cm x 10 cm x 12cm PVC box, with attached stainless steel’s activated carbon felt as electrodes and rice washing water (RWW) as control substrate and with high clay content soil in fixed 10 cm soil level. The experiment was conducted for 3 months duration and multimeter was used to record the voltage output of SMFC. Total Bacteria Count (TBC) analysis was also conducted to study the relationship between number of microorganisms and voltage generation (mV). Combined effects of SMFC were observed at the end of the experiment. Throughout the study, it was found that the SMFC with 10 cm water depth, 5 cm electrode spacing and using only rice washing water (RWW) as substrate without any addition of other substrate was to be the best condition with the maximum voltage output of 711 mV. Moreover, with TBC analysis, this setup has proven that the more the number of microorganisms in the fuel cell, the higher the voltage output (mV) as it has the highest amount of microorganisms up to 141 × 10⁶ of microorganisms at its highest voltage output’s peak.
Keywords: fossil fuel consumption; Soil Microbial Fuel Cell; bioelectricity; microorganism; voltage output